2010
DOI: 10.1590/s0085-56262010000400021
|View full text |Cite
|
Sign up to set email alerts
|

Nyssomyia intermedia (Lutz & Neiva) and Nyssomyia neivai (Pinto) (Diptera, Psychodidae, Phlebotominae) in a sympatric area: seasonal and nocturnal hourly rhythm in black and white modified Shannon traps

Abstract: ABSTRACT. Nyssomyia intermedia (Lutz & Neiva) and Nyssomyia neivai (Pinto) (Diptera, Psychodidae, Phlebotominae) in a sympatric area: seasonal and nocturnal hourly rhythm in black and white modified Shannon traps. Captures with black and white Shannon traps were undertaken to identify aspects of the behavior of the two cryptic and sympatric species implicated as vectors of cutaneous leishmaniasis, Nyssomyia intermedia (Lutz & Neiva, 1912) and Nyssomyia neivai (Pinto, 1926). The traps were installed side by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
3
15
0
1
Order By: Relevance
“…A total of 65.0% of the sand flies were collected inside the forest, unlike other studies, in which most specimens were found in anthropic environments (Saraiva et al 2008;Galati et al 2010). This fact may be due to the use of a Shannon trap in the forest and CDC light traps in the other environments, which demonstrates the importance of using more than one type of trap in studies of sand fly fauna.…”
Section: Resultsmentioning
confidence: 79%
“…A total of 65.0% of the sand flies were collected inside the forest, unlike other studies, in which most specimens were found in anthropic environments (Saraiva et al 2008;Galati et al 2010). This fact may be due to the use of a Shannon trap in the forest and CDC light traps in the other environments, which demonstrates the importance of using more than one type of trap in studies of sand fly fauna.…”
Section: Resultsmentioning
confidence: 79%
“…This trend was also observed for the Ny. neivai by Galati et al (2010), but not for the either species by Massafera et al (2005), whose peaks occurred only during the rainy season. On the other hand, Ny.…”
Section: Discussionmentioning
confidence: 80%
“…A similar result was found in the Ribeira Valley in SP for Ny. neivai (Galati et al 2010); however, the black trap attached significantly more Ny. whitmani than the white trap on the Bodoquena Range in the state of Mato Grosso do Sul (MS) (Galati et al 2001).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations